2017
DOI: 10.1007/s13770-017-0079-5
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Potential of Platelet Rich Fibrin (PRF) for Curing Intrabony Periodontal Defects: A Systematic Review of Clinical Studies

Abstract: Platelet-rich fibrin (PRF) has been used in regenerative medicine and dentistry. Recently, its use has been advocated for regenerative periodontics and wound healing. The randomized control trials have assessed the regenerative efficacy of the PRF for restoring intrabony periodontal defects. The objectives are to critically analyze and appraise the currently available literature, focusing on the use of PRF in regenerating periodontal bone defects. An electronic search was conducted (PubMed/MEDLINE, Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Table 3 and Table 4 describes in detail the features of the SRs included. Four SR included only studies on PRP [ 21 , 22 , 23 , 24 ] (one of them included a study on “platelet pellet” that the authors considered as a PRP preparation) [ 21 ], five on PRF only [ 25 , 26 , 27 , 28 , 29 ] and five on platelet concentrates irrespective of their type (PRP/PRF and, in one case, PRP/PRF/PRGF) [ 22 , 30 , 31 , 32 , 33 ]. All the SRs included exclusively randomized controlled trials (RCT) on the use of APCs in the treatment of intraosseous defects.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 and Table 4 describes in detail the features of the SRs included. Four SR included only studies on PRP [ 21 , 22 , 23 , 24 ] (one of them included a study on “platelet pellet” that the authors considered as a PRP preparation) [ 21 ], five on PRF only [ 25 , 26 , 27 , 28 , 29 ] and five on platelet concentrates irrespective of their type (PRP/PRF and, in one case, PRP/PRF/PRGF) [ 22 , 30 , 31 , 32 , 33 ]. All the SRs included exclusively randomized controlled trials (RCT) on the use of APCs in the treatment of intraosseous defects.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it decreases expression of alkaline phosphatase (ALP) activity, osteocalcin (OCN) and bone sialoprotein (BSP) while up-regulating collagen-I and cementum-derived protein-23 [ 212 ]. The use of platelet-rich fibrin has been reported for various tissue regeneration applications including wound healing [ 213 , 214 ], periodontal defects [ 215 , 216 , 217 ], bone regeneration [ 218 , 219 , 220 , 221 ].…”
Section: Biomimetic Tissue-engineering Aspectsmentioning
confidence: 99%
“…Better outcomes related to immediate implant loading Anitua 27 Early osseointegration Improved bone apposition around implant Anitua 27 , Georgakopoulos et al 25 Helps in bone regeneration around immediate implant Najeeb et al 55 Preservation of alveolar height during multiple extractions Borie et al 7 , Naik et al 56 Treatment of gingival recession with flap surgery in mandibular anterior teeth Mishra et al 57 PRF used successfully under periodontic endodontic furcation defects Mishra et al 57 PRF positioned under modified coronal advanced flap showed overwhelming results in 6 month's follow-up Gupta et al 58 , Borie et al 7 , Miron Fujiioka et al (2017) PRF in sockets with titanium membranes applied on the walls with primary closure showed adequate bone filling in 8 week's follow-up Keswani et al 59 PRF used in reconstruction protocols with freeze-dried bone allograft with graft or implant loss Simonpieri et al 60 PRF in localized osteitis 90% closure was found at the surgical sites Hoaglin and Lines 61 The effect of PRP and PRF is almost same in periodontal regeneration Suchetha et al 19 Optional treatment of choice in elderly patients as PRF has good healing and regeneration properties with complete resorption after surgery Cortese et al 62 Potential ideal scaffold in revascularization of immature permanent teeth with necrotic pulp tissues Keswani et al 59 PRF improves dental pulp proliferation and revitalization of tooth with necrotic pulp tissues Hotwani and Sharma 63 Bisphosphate-related osteonecrosis of the jaw with PRP/PRF with bone resection is found to be effective and alternative treatment Sarkarat et al 64…”
Section: Improves Implant Prognosismentioning
confidence: 99%